2004
DOI: 10.1080/10635150490265085
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography Explains Cophylogenetic Patterns in Toucan Chewing Lice

Abstract: Historically, comparisons of host and parasite phylogenies have concentrated on cospeciation. However, many of these comparisons have demonstrated that the phylogenies of hosts and parasites are seldom completely congruent, suggesting that phenomena other than cospeciation play an important role in the evolution of host-parasite assemblages. Other coevolutionary phenomena, such as host switching, parasite duplication (speciation on the host), sorting (extinction), and failure to speciate can also influence hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
89
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 40 publications
(53 reference statements)
7
89
0
Order By: Relevance
“…Yet, this study suggests that co-speciation might not be observed at a higher phylogenetic scale (i.e., over a longer time period) if host specificity is not limited to a single host species. Indeed, regional codifferentiation with different closely related host species might rather ultimately mix the co-differentiation signal if the different host species overlap partially in their distribu-tion ranges and if the parasite life history traits, such as in Heligmosomoides, authorize host switching events between syntopic host species (Weckstein, 2004). In addition, the signal of regional co-differentiation, if generated by differences in the regional abundance of the different hosts, might also be lost if the relative regional host abundance changes over evolutionary time.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, this study suggests that co-speciation might not be observed at a higher phylogenetic scale (i.e., over a longer time period) if host specificity is not limited to a single host species. Indeed, regional codifferentiation with different closely related host species might rather ultimately mix the co-differentiation signal if the different host species overlap partially in their distribu-tion ranges and if the parasite life history traits, such as in Heligmosomoides, authorize host switching events between syntopic host species (Weckstein, 2004). In addition, the signal of regional co-differentiation, if generated by differences in the regional abundance of the different hosts, might also be lost if the relative regional host abundance changes over evolutionary time.…”
Section: Resultsmentioning
confidence: 99%
“…The second is that most common among these flies. Historical associations of lice and some mites with their hosts may have many cospeciation/codivergent events, exceptions to which may be explained by phoresia (Weckstein 2004). Cophylogenetic analyses of other, second-group, ectoparasitic arthropods (fleas and ticks) with preparasitic stages in the roost or environment of their mammal hosts, find a low probability of cospeciation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report a partial or no fit between the parasite and host phylogenies in more complex situations, involving parasites infecting multiple hosts. This is the case for Monogenea and fish , lice and passerine birds (Johnson et al, 2002), chewing lice and toucans (Weckstein, 2004), and chewing lice and penguins (Banks et al, 2006).…”
Section: Introductionmentioning
confidence: 99%